Computational Experiments: A New Analysis Method for Cyber-Physical-Social Systems - Xue, Xiao; Shen, Yifan; Yu, Xiangning; Zhou, De-Yu; Wang, Xiao; Wang, Gang; Wang, Fei-Yue (IEEE transactions on systems, man, and cybernetics. Systems, 2024)
Given the complex nature of cyber-physical-social systems (CPSSs), understanding their mechanism is essential for analyzing and controlling their actions while minimizing potential harm. However, studying CPSS in the real world is costly and constrained by legal and institutional factors. Computational experiments have emerged as a new method for quantitative analysis, and this article proposes a method of using computational experiments for analyzing CPSS, which consists of model docking, experiment design, and experiment analysis. The cloud manufacturing service ecosystem (CMSE) is used as a typical case study to verify the effectiveness of the proposed method by simulating different operation strategies. The results show that the computational experiments method is effective in providing new means and ideas for analyzing CPSS.